Implementation of the Merdeka Curriculum and Integration of ICT Competences in English Lessons at Senior High School - Yahya, Aliya Izet Begovic; Mutakin, Tatan Zenal; Sajiman, Supardi Uki; Wahid, Sunar (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2025)
As Indonesian schools transition toward the Merdeka Curriculum’s student-centered approach, understanding how Information and Communication Technology (ICT) is integrated into English language learning is increasingly critical. This study aims to explore the implementation of the Merdeka Curriculum and the integration of ICT based on the UNESCO framework in English language learning at public high schools in the Greater Jakarta area, specifically SMAN 1 Bekasi, SMAN 5 Bekasi, SMAN 1 Depok, and SMAN 48 Jakarta. The Merdeka Curriculum, introduced to provide flexibility in learning, is expected to enhance students' competencies and character through a more adaptive approach to individual needs. One important aspect of this curriculum is the utilization of ICT, which is expected to enrich the interaction between teachers and students and improve access to information. This research employs a qualitative approach with a case study methodology to examine how teachers understand and implement the curriculum and the extent to which ICT is integrated into English language learning, while descriptive statistical analysis is used to analyze the questionnaires. Based on interviews, observations, and document analysis, the results show that the majority of teachers have understood the Merdeka Curriculum, but its implementation remains inconsistent. The main challenges faced include limited resources, insufficient training, and inadequate technology readiness. Furthermore, support from school leaders and the availability of adequate ICT facilities are crucial factors in the successful implementation of this curriculum. Although the use of ICT in teaching is present, it has not been fully optimized. This study suggests the need for appropriate strategies and full support from schools to overcome these challenges. The implementation of the Merdeka Curriculum has great potential to improve the quality of education, but it requires careful planning and better infrastructure development.